Personality and Adjustment Effect of Join Family Children: A Comparative Analysis of Transition Issues in Joint Family and Nuclear Family Adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Adjustment is the critical factor of adolescent life. The teens belonging to separate family framework have different transition actions. Adolescent age is the age at which each adolescent weave daydream, stay in the imitation universe. When an individual changes in the community in any case, only then he can lead a wonderful life. The aim of the present research was to analyses the contrast between transition issues of joint family adolescents and nuclear family adolescents. The sample of the analysis consisted of 50 senior high school students.